2020
DOI: 10.3390/met10111455
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of NiSn-rGO Composite Coatings from Deep Eutectic Solvents and Their Physicochemical Characterization

Abstract: The present work describes, for the first time, the electrodeposition of NiSn alloy/reduced graphene oxide composite coatings (NiSn-rGO) obtained under pulse current electrodeposition conditions from deep eutectic solvents (choline chloride: ethylene glycol eutectic mixtures) containing well-dispersed GO nanosheets. The successful incorporation of the carbon-based material into the metallic matrix has been confirmed by Raman spectroscopy and cross-section scanning electron microscopy (SEM). A decrease in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The assessment of the corrosion performance showed that Sn-rGO composite coatings presented better protective characteristics during long exposure periods to 0.5 M NaCl aggressive solution as compared to pure Sn. Rosoiu et al [58] investigated the electrodeposition of NiSn-rGO composite coatings from choline chloride: ethylene glycol (1:2 molar ratio) deep eutectic solvent using pulsed current conditions. Dispersed ammonia functionalized GO has been involved to prepare the electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of the corrosion performance showed that Sn-rGO composite coatings presented better protective characteristics during long exposure periods to 0.5 M NaCl aggressive solution as compared to pure Sn. Rosoiu et al [58] investigated the electrodeposition of NiSn-rGO composite coatings from choline chloride: ethylene glycol (1:2 molar ratio) deep eutectic solvent using pulsed current conditions. Dispersed ammonia functionalized GO has been involved to prepare the electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the apparent complexity of such processes, there have been relatively few studies in this area. In particular, a single study [75] has been published investigating the incorporation of reduced graphene oxide particles into an electrodeposited matrix of the nickel alloy NiSn (NiSn-rGO composite) using an ethaline-based electrolyte. Under pulse current conditions, high-quality NiSn-rGO composite films were cathodically deposited, exhibiting satisfactory adhesion to the copper substrate.…”
Section: Nickel-based Compositesmentioning
confidence: 99%
“…The electrodeposition of tin with conventional aqueous electrolytes is accompanied by a hydrogen evolution reaction. The electrodeposition in deep eutectic solvents (DESs) has attracted much attention, and DESs are acknowledged as a promising new form of iconic liquid (ILs) that share many similar properties including wide potential windows, low vapor pressures, no hydrogen evolution reaction, and compositional tunability. ,− …”
Section: Introductionmentioning
confidence: 99%